The Implications of an Evolutionary Perspective on Mental Health Promotion - Joyce, Andrew; Howat, Peter; Maycock, Bruce (The Clifford Beers Foundation, 2005)
Although Darwin formulated his theory of evolution in the nineteenth century, it is only recently that evolutionary theories have penetrated medicine (Nesse & Williams, 1995) and health promotion (Eaton, Strassman et al, 2002). This paper examines the implications of an evolutionary perspective for mental health promotion. Borrowing from the literature of evolutionary psychopathology, neuroendocrinology and social determinants of health, it will show how an evolutionary perspective reveals that mental health promotion can assist in reducing the prevalence of depression and cardiovascular disease. An evolutionary perspective can also provide direction for mental health promotion policy and program development.